Branched-chain amino acid supplementation and voluntary running have distinct effects on the serum metabolome of rats with high or low intrinsic aerobic capacity - Karvinen, Sira; Korhonen, Tia-Marje K.; Kiviö, Ronja; Lensu, Sanna; Gajera, Bharat; Britton, Steven L.; Koch, Lauren G.; Nieminen, Anni I.; Kainulainen, Heikki (Frontiers in Nutrition, 2024)
A growing body of literature associates branched-chain amino acid (BCAA) catabolism to increased fatty acid oxidation and better metabolic health. Hence, BCAA-rich diets may improve body composition and muscle protein synthesis. However, the role of individual characteristics such as a low aerobic fitness, a well-established risk factor for cardio-metabolic diseases, has not been studied.This study examined 64 female rats from the high-capacity runner (HCR) and lowcapacity runner (LCR) rat model. Rats from each line (HCR or LCR) were divided into four groups; differing from diet (CTRL or BCAA) and from the opportunity to voluntarily run on a running wheel (NONRUNNER or RUNNER). Groups were matched for body mass and maximal running capacity within each line. We measured maximal running capacity and metabolism before and after the intervention of diet and voluntary running activity. After the end of the experiment, serum samples were collected for metabolome analysis.We are the first to show that BCAA supplementation has a more pronounced impact on LCRs compared to HCRs. Specifically, in LCR rats, BCAA supplementation led to reduced daily voluntary running distance and an enrichment of serine metabolism in the serum metabolome. While voluntary running increased food intake and energy expenditure, its effects on the serum metabolome were minimal in HCRs.The present research highlights the benefit achieved by combining BCAA supplementation with running activity, especially in the LCR line. Importantly, our results underscore the interconnected role of BCAAs and fatty acid metabolism in promoting overall metabolic health.